Survey Research: Do All RN Types Have the Same Perceptions Regarding Professional Nursing Governance?. (14th May 2022) - Speroni, Karen Gabel; Budhathoki, Chakra; Walters, Cynthia; Dutton, Suzanne; Mackay, Periwinkle; Oguariri, Raphael M.
Abstract : OBJECTIVE: Researchers examined professional nursing governance perception differences by RN type (clinical, manager, and other RNs), and nurse-related outcome associations. BACKGROUND: Shared governance is associated with improved nurse-related outcomes. Understanding differences in RN types regarding shared governance perceptions is important and not well studied. METHODS: Mean Index of Professional Nursing Governance (IPNG) scores from 3 hospitals' 502 RNs were used to evaluate associations by RN type and unit-based nurse-related outcomes. Descriptive and inferential statistical methods were used. RESULTS: Shared governance was the predominant finding (overall score and 4 of 6 subscale scores) with no significant differences by RN type. Traditional governance was scored for 1 subscale (control over personnel), which was not significant. There were no significant differences in the IPNG score associations with outcomes data by RN type. CONCLUSIONS: Clinical nurses, managers, and other RN types perceived their governance as shared, without significant difference in the nurses' perceptions based on role.